Diversity als pädagogische Herausforderung aus osteuropäischer Sicht - Michail Pevsner (International Dialogues on Education: Past and Present, 2016)
The article considers major elements of the pedagogical metatheory of diversity in educationa systems as a new area of research by international comparison. Nowadays there are numerous studies in various countries that examine specific ways of dealing with different dimensions of diversity. The author analyzes the educational transition of post-Soviet countries from the diversity of specific pedagogical concepts, models and stratgies to the devlopment of a complex metatheory of diversity. The development of this metatheory is influenced by American and Western European researchers’ theoretical studies, as well as intensive project work in which Russia and other Eastern European countries are heavily involved. In the article a transdisciplinary methodology is suggested as the scientific foundation of this metatheory. This approach surpasses the limits of interdisciplinary connections between subject disciplines and requires a complex examination of diversity in society, culture, science, and economic and education systems. The article looks at the most important posits of metathory, for example: a broad philosophical and pedagogical vision of inclusive education, organizational diversity of educational institutions which deal with heterogeneity, education for „rational“ tolerance as opposed to absolute tolerance.